2011
DOI: 10.1007/s10611-011-9314-5
|View full text |Cite
|
Sign up to set email alerts
|

Iraq and the case for Australian war crimes trials

Abstract: This article presents the case for Australian war crimes trials, following

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Contrary to the view of the Prosecutor's Office, we found that there are international courts says that the crimes committed in Iraq, are (international crimes), including the Grand Chamber Court of European Human Rights, which issued its judgment in the case of (al -Skeini and others v. U. K), condemned U. K for the killing of six civilians during military operations carried out by British soldiers in Iraq in 2003 (18) and its judgment in the case of (Hilal Abdul Razzaq Ali al -Jedda v. U. K) (19), condemned U. K for the internment three years of Iraqi civilian by British forces in Iraq so how does the Prosecutor Office refer to the acts committed in Iraq as unserious crimes ? Also, many international organizations deemed what is happening in Iraq, of atrocities of the international humanitarian law, a crimes against humanity, including Amnesty International, which cited reports to those atrocities committed by military and civilian overseas forces in Iraq, particularly the case of arbitrary detention for long periods without trial, and torture or inhuman treatment, and causing widespread destruction to property and seizes them, as well as attacking and bombing the cities and hospitals (20), also another report indicates that (unlike the air Force, the U. S. and the U. K land forces used bombs and cluster ammunitions widely in civilian populated areas along the way to Baghdad), and these weapons explode and spread hundreds of small bombs, which covers an area of 2,3 of a football field (21), not to mention what resulted from the war of the migration of large numbers of citizens till this event described by the UN High Commissioner for refugees (UNHCR) that the world is witnessing a dangerous process of displacement since the tragic events that occurred in 1948 (22).…”
Section: -Report Of the Otp In The Situation In Iraqmentioning
confidence: 99%
“…Contrary to the view of the Prosecutor's Office, we found that there are international courts says that the crimes committed in Iraq, are (international crimes), including the Grand Chamber Court of European Human Rights, which issued its judgment in the case of (al -Skeini and others v. U. K), condemned U. K for the killing of six civilians during military operations carried out by British soldiers in Iraq in 2003 (18) and its judgment in the case of (Hilal Abdul Razzaq Ali al -Jedda v. U. K) (19), condemned U. K for the internment three years of Iraqi civilian by British forces in Iraq so how does the Prosecutor Office refer to the acts committed in Iraq as unserious crimes ? Also, many international organizations deemed what is happening in Iraq, of atrocities of the international humanitarian law, a crimes against humanity, including Amnesty International, which cited reports to those atrocities committed by military and civilian overseas forces in Iraq, particularly the case of arbitrary detention for long periods without trial, and torture or inhuman treatment, and causing widespread destruction to property and seizes them, as well as attacking and bombing the cities and hospitals (20), also another report indicates that (unlike the air Force, the U. S. and the U. K land forces used bombs and cluster ammunitions widely in civilian populated areas along the way to Baghdad), and these weapons explode and spread hundreds of small bombs, which covers an area of 2,3 of a football field (21), not to mention what resulted from the war of the migration of large numbers of citizens till this event described by the UN High Commissioner for refugees (UNHCR) that the world is witnessing a dangerous process of displacement since the tragic events that occurred in 1948 (22).…”
Section: -Report Of the Otp In The Situation In Iraqmentioning
confidence: 99%
“…This is particularly the case with regard to Australian military activities regarding the fl ow of weapons from Australia to the region and the Australian involvement in the 2003 invasion and occupation of Iraq; no inquiry has taken place to 'refl ect back on the reasons, circumstances and decision-making procedures by which a country went to any war, and to consider its consequences' (Thakur, 2012 :17). There are as well widespread allegations of crime against humanity committed by the military and civilian contractors overseas, including the mass killings of Iraqis during and after the 1991 Gulf War; killings by the Special Air Service (SAS), described as a 'turkey shoot', in Iraq before President Bush's 48-hour ultimatum to Saddam Hussein; the killing of civilians in the attacks on the city of Fallujah in late 2004; and the role of Australians in the US 'rendition' programme of kidnapping and the torture of suspects in Iraq, Afghanistan, and elsewhere in the world in the wake of 9/11 (Cantwell & Bearup, 2013 ;Davies, Snow, & Jopson, 2011 ;Doran & Anderson, 2011 ;Kevin, 2004 ;. FOI requests have increasingly been frustrated by government efforts to hide the truth, as in the case of the Australian Wheat Board bribes of more than $300 million dollars to Saddam Hussein.…”
Section: Human Rightsmentioning
confidence: 99%